(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Airoldi (1930, 1932) described twenty-three fossil Corallinales (Rhodophyta) from the Oligocene of the Tertiary Piedmont Basin (NW Italy), containing thirteen new species. In this paper Archaeolithothamnium praeerithraeum Airoldi 1932 and Archaeolithothamnium statiellense Airoldi 1932 are re-documented and re-described. The features observable in the sporangial compartments allowed to attribute both species to the genus Sporolithon.